2020
DOI: 10.1111/ddg.14156
|View full text |Cite
|
Sign up to set email alerts
|

Immunizations in immunocompromised patients: a guide for dermatologists

Abstract: The increasingly frequent use of immunomodulatory agents in dermatology requires the observance of specific recommendations for immunization. These recommendations are developed and regularly updated by the German Standing Committee on Vaccination (STIKO), an independent advisory group at the Robert Koch Institute. Dermatological patients on immunosuppressive treatment should ideally receive all vaccinations included in the standard immunization schedule. Additionally, it is recommended that they also undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 59 publications
0
24
0
3
Order By: Relevance
“…Higher affinity and avidity IgG antibodies can be detected after 10–14 days, with maximum titers taking up to 4–6 weeks [ 21 ]. A minimum period of 2 weeks, up to 4 weeks, is generally recommended before (re-)initiation of the immunosuppressive/immunomodulatory treatment [ 69 ]. For drugs given in dosage intervals of ≥4 weeks, administration of vaccines midcycle or 2 weeks before the next dose seems a reasonable option [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher affinity and avidity IgG antibodies can be detected after 10–14 days, with maximum titers taking up to 4–6 weeks [ 21 ]. A minimum period of 2 weeks, up to 4 weeks, is generally recommended before (re-)initiation of the immunosuppressive/immunomodulatory treatment [ 69 ]. For drugs given in dosage intervals of ≥4 weeks, administration of vaccines midcycle or 2 weeks before the next dose seems a reasonable option [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Additionally, these studies indicate that rituximab recipients are not at increased risk of inactivated vaccine-related adverse effects. 3 Recently, a prospective clinical trial evaluated the effect of ocrelizumab (humanized anti-CD20 antibody) on the immunogenicity of several vaccines that were administered 12 weeks after infusion. 4 This study showed increased seroprotection rates across all studied vaccines in ocrelizumab recipients, although these conversion rates are lower than those observed in control individuals.…”
mentioning
confidence: 99%
“…Consensus guidelines recommend administering routine vaccinations (eg, tetanus, diphtheria, and pertussis [TDaP]) at least 4 weeks before rituximab initiation. 3 Notably, they recommend administering inactivated influenza vaccine even in individuals undergoing active treatment with rituximab, because patients face imminent risk of contracting influenza, which outweighs the minimal risks associated with vaccination. 3 Importantly, there are no studies addressing the immunogenicity of live attenuated vaccines, given theoretical safety concerns regarding the use of live attenuated vaccines in rituximab recipients.…”
mentioning
confidence: 99%
See 2 more Smart Citations